Comparison refurbishment models of district heating networks - Kuprys, Algirdas; Gatautis, Ramūnas (Journal of Civil Engineering and Management, 2013)
The renovation of multi-storey residential buildings reduces heat consumption intensity and decreases heat demand, which may have a harmful effect on a district heating supply system. The paper analyses the heat loss change in four district heating distribution networks (DHNs) of Kaunas at the various scenarios of buildings and DHN renovation stages. A bundle of genetic algorithm software package was used to carry out the districts’ distribution network hydraulic calculations in the case of building renovation without changing the hydrodynamic and network routes. The experimental data were used to calculate heat loss for old and new pipes. The computer data of networks used to summarise the cost of DHN then for the renovation of buildings as well as for renovation progress will go evenly with DHN refurbishment. Network optimization results were summarised by functional dependence. The comparison of the projects’ efficiency was analysed in the following cases: the diameters of pipes of DHN were not changed, new diameters of pipes were integrated partly after partial residential buildings renovation and after a complete renovation of residential building and optimisation of pipeline diameters. The efficiency of separate guidelines of the DHN refurbishment project was summarised by performing sensitivity analysis.